Measurement and comparison of thermal conductivity of porous materials using box, dual-needle, and single-needle probe methods-A case study. (November 2020) - Kim, Daehoon; Oh, Seokhoon
Abstract: Thermal conductivity controls heat transfer through materials, so accurate assessment of thermal conductivity is necessary when modeling the thermal behavior of a material. In this study, the thermal conductivities of a silty clay specimen, a sand specimen, and six types of mortar specimens with various mixing ratios of sand as an additive, were measured using box, dual-needle, and single-needle probes, with and without thermal grease, under saturated and oven-dried conditions. The results obtained with the needle probes were compared to those measured using the box probe, given the high accuracy of the box probe method. After applying thermal grease to single- and dual-needle probes, the thermal contact resistance decreased, resulting in increased thermal-conductivity values for soil and mortar specimens under saturated (wet) and oven-dried conditions. The thermal-conductivity values measured via the single-needle probe were as accurate as those measured by the box probe, whereas those measured using the dual-needle probe underestimated the material's thermal conductivity. Further research is required regarding thermal-conductivity measurements and the design of the tests and equipment used. The results of this study provide useful information for future studies of thermal-property measurements and probe development.